Mucinous Cystadenoma of the Testis: A Case Report with Immunohistochemical Findings - Gilhyang Kim; Dohee Kwon; Hee Young Na; Sehui Kim; Kyung Chul Moon (Korean Society of Pathologists & the Korean Society for Cytopathology, 2017)
Mucinous cystadenoma of the testis is a very rare tumor. Herein, we report a case of mucinous cystadenoma arising in the testis of a 61-year-old man, along with a literature review. Computed tomography showed a 2.5-cm-sized poorly enhancing cystic mass. Grossly, the tumor was a unilocular cystic mass filled with mucinous material and confined to the testicular parenchyma. Histologically, the cyst had a fibrotic wall lined by mucinous columnar epithelium without atypia. Immunohistochemical staining was positive for cytokeratin 20 and CDX2, as well as focally positive for cytokeratin 7. The pathologic diagnosis was mucinous cystadenoma.